2017
DOI: 10.1080/21655979.2016.1267884
|View full text |Cite
|
Sign up to set email alerts
|

Expression of thermostable β-xylosidase in Escherichia coli for use in saccharification of plant biomass

Abstract: The present work is aimed to evaluate the saccharification potential of a thermostable b-xylosidase cloned from Bacillus licheniformis into Escherichia coli for production of bioethanol from plant biomass. Recombinant b-xylosidase enzyme possesses the ability of bioconversion of plant biomass like wheat straw, rice straw and sugarcane bagass. By using this approach, plant biomass that mainly constitute cellulose can be converted to reducing sugars that could then be easily converted to bioethanol by simple fer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 25 publications
1
5
0
Order By: Relevance
“…It might be because of the reason that with additional rise in incubation time, either the process of product inhibition comes into action due to accretion of glucose and cellobiose, or due to less availability of free cellulose with the passage of time. Results of this research are in accordance with those of Aftab et al (2017) that highest saccharification of sugarcane bagasse was observed after 6 h of incubation using thermophilic cellulases. These alike results can be attributed to the reason that thermophilic cellulases act more energetically and that when an amalgam of enzymes is employed for saccharification, the overall reaction time for hydrolysis is lessened ( Shokrkar and Ebrahimi, 2018 ).…”
Section: Resultssupporting
confidence: 91%
“…It might be because of the reason that with additional rise in incubation time, either the process of product inhibition comes into action due to accretion of glucose and cellobiose, or due to less availability of free cellulose with the passage of time. Results of this research are in accordance with those of Aftab et al (2017) that highest saccharification of sugarcane bagasse was observed after 6 h of incubation using thermophilic cellulases. These alike results can be attributed to the reason that thermophilic cellulases act more energetically and that when an amalgam of enzymes is employed for saccharification, the overall reaction time for hydrolysis is lessened ( Shokrkar and Ebrahimi, 2018 ).…”
Section: Resultssupporting
confidence: 91%
“…1. Other reports 42–46 are present on the cloning and expression of xylosidase gene in E. coli from various sources but till now no report is present on the cloning and expression of xylosidase gene from C. clariflavum .…”
Section: Discussionmentioning
confidence: 99%
“…43,89,96,97 Effect of recombinant xylosidase on the hydrolysis of wheat straw was observed in similar pattern like higher percentage hydrolysis (8.91%) again pretreated wheat straw biomass. Many reports are present on the plant biomass hydrolysis by xylosidase enzyme from various microorganisms 20,45,84,98–100 but not any report on hydrolysis of recombinant xylosidase enzyme from C. clariflavum yet present.…”
Section: Discussionmentioning
confidence: 99%
“…pET expression vectors contain the T7 promoter system and are frequently utilized for the heterologous expression of proteins. 20–24…”
Section: Introductionmentioning
confidence: 99%